Thai traditional painting - Lyons, Elizabeth (Fine Arts Department, 1963)
Studies the details and backgrounds relevant to Thai traditional painting inside several Wats in Thailand. Analyzes the painting styles, origins, appearances, narrations and techniques used in the creation of Thai painting specimen with provided connection to other painting styles from other civilization and comparison to other paintings in other countries.